(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: The relationship between public expenditure and revenue that determines the budget balance in the explanation of budget deficits is very important. This study aimed to examine the association between public spending and income in Turkey. Methodology: This article applies the continuous wavelet transform method (CWT) to study the relationship between government revenues and expenditures in Turkey. The study, which covers the period 2006-2020, consists of monthly data. The following four CWT tools were used in the analysis: Wavelet Power Spectrum, Cross Wavelet Power, Wavelet Coherence, and Phase Difference. Results: The results of the study, controlling taxes rather than expenditures, play a key role in reducing fiscal deficits in Turkey in the short term. It is revealed that the dynamics of the budget balance in the medium term can be explained by the spend-tax hypothesis and that the tax burden can be alleviated by spending cuts. In the long term, results were obtained that support the spend-tax hypothesis. Conclusion: The paper reveals that taxes play an important role in controlling budget deficits in the short run. It turns out that the dynamics of the budget balance can be explained in the medium term by expenditure cuts and then the tax burden can be alleviated. In the long run, implementing fiscal policies based on public spending rather than taxation will be more effective against budget deficits.